2020
DOI: 10.1002/chem.202000708
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Carbon‐Based 2D Nanostructures for Enhanced Photocatalytic CO2Reduction: A Dimensionality Perspective

Abstract: Photocatalytic CO 2 reduction is ar evolutionary approach to solve imminent energy and environmental issues by replicating the ingenuity of nature. The past decadeh as witnessed an impetus in the rise of two-dimensional (2D) structure materials as advanced nanomaterials to boost photocatalytic activities. In particular,t he use of 2D carbonbased materials is deemed as highly favorable, not only as a green material choice, but also due to their exceptional physicochemical and electricalp roperties. This Review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 143 publications
(48 citation statements)
references
References 286 publications
(177 reference statements)
0
48
0
Order By: Relevance
“…Because of its excellent optical properties, low cost, and good stability, graphitic carbon nitride (g-C3N4) has attracted much scientific interest in the field of photocatalysis. [42][43][44][45][46][47][48][49][50][51][52][53] Dong et al have reported the application of the NVs-incorporated g-C3N4 (V-g-C3N4) for photoreduce N2. 54 They found that the N2 adsorption amount of V-g-C3N4 was 75.1 cm 3 g -1 , 2.4 times higher than that of g-C3N4 without NVs (30.9 cm 3 g -1 ), which suggested that the NVs on the surface of V-g-C3N4 could provide a number of chemisorption and activation sites for N2 molecules, leading to an NH3 production rate of 1.24 mmol h -1 gcat -1 under visible light irradiation in the presence of methanol as a hole scavenger.…”
Section: Defect Engineeringmentioning
confidence: 99%
“…Because of its excellent optical properties, low cost, and good stability, graphitic carbon nitride (g-C3N4) has attracted much scientific interest in the field of photocatalysis. [42][43][44][45][46][47][48][49][50][51][52][53] Dong et al have reported the application of the NVs-incorporated g-C3N4 (V-g-C3N4) for photoreduce N2. 54 They found that the N2 adsorption amount of V-g-C3N4 was 75.1 cm 3 g -1 , 2.4 times higher than that of g-C3N4 without NVs (30.9 cm 3 g -1 ), which suggested that the NVs on the surface of V-g-C3N4 could provide a number of chemisorption and activation sites for N2 molecules, leading to an NH3 production rate of 1.24 mmol h -1 gcat -1 under visible light irradiation in the presence of methanol as a hole scavenger.…”
Section: Defect Engineeringmentioning
confidence: 99%
“…Photocatalytic reactions such as H 2 production, CO 2 reduction, H 2 O 2 production, N 2 fixation, waste remediation, photocatalysis of organic reaction, and photocatalytic sensors are conducted to mimic natural photosynthesis involving solar energy. [82][83][84][85] Key processes for photocatalysis include 1) light harvesting; 2) photogenerated electron-hole pairs separation and transportation; 3) reduction reaction with electron or oxidation reaction with hole. [86] Integrating with photosensitizer and catalytic sites in a single crystal, titanium-based MOFs are a kind of promising photocatalysts that possess excellent light-harvesting and catalytic ability.…”
Section: Photocatalytic Applicationsmentioning
confidence: 99%
“…[ 21–23 ] To increase the photocatalytic performance, some scientists have contributed to modify GCN to solve these two problems, which is usually accompanied with band energy level modulation, crystal structure modification, morphology, and composition control. [ 16,24–26 ]…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] To increase the photocatalytic performance, some scientists have contributed to modify GCN to solve these two problems, which is usually accompanied with band energy level modulation, crystal structure modification, morphology, and composition control. [16,[24][25][26] DOI: 10.1002/solr.202000610 Graphitic carbon nitride (GCN) has become an attractive photocatalyst for solar energy conversion, but the photocatalytic activity of GCN is still limited by the extremely fast electron-hole recombination. Herein, a defective ultrathin mesoporous graphitic carbon nitride (DUMCN) photocatalyst with high specific surface area and mesoporous structure is fabricated through a facile three-step heat-treatment strategy, which reduces the distance of bulk photogenerated carriers to the surface, resulting in efficient adsorption and diffusion of reactants and products, and exposing adequate surface active sites.…”
Section: Introductionmentioning
confidence: 99%